2017
DOI: 10.1038/bjc.2017.228
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing revealed novel prognostic biomarkers and promising targets for therapy of ovarian clear cell carcinoma

Abstract: Background:Ovarian clear cell carcinoma (OCCC) is mostly resistant to standard chemotherapy that results in poor patient survival. To understand the genetic background of these tumours, we performed whole-genome sequencing of OCCC tumours.Methods:Tumour tissue samples and matched blood samples were obtained from 55 Japanese women diagnosed with OCCC. Whole-genome sequencing was performed using the Illumina HiSeq platform according to standard protocols.Results:Alterations to the switch/sucrose non-fermentable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 40 publications
4
72
1
2
Order By: Relevance
“…Y220C, I254S, C242F, and G245S mutations in this study were previously described (Shpak, Goldberg, & Cowperthwaite, 2014) in lung cancer, esophageal squamous cell carcinoma, ovarian cancer, and colorectal carcinoma. Itamochi et al (2017) reported that aberrant RTK signaling was closely associated with prognosis of ovarian clear cell carcinoma and the 3-year survival rate in patients with activated RTK signaling was higher than that of patients with inactivated RTK signaling (91% vs. 53%, hazards ratio 0.35 [95% CI: 0.13-0.94], p = 0.0373). This study found comparable rates of mutation in the RTK signaling pathway in drug-resistant and -sensitive recurrent ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Y220C, I254S, C242F, and G245S mutations in this study were previously described (Shpak, Goldberg, & Cowperthwaite, 2014) in lung cancer, esophageal squamous cell carcinoma, ovarian cancer, and colorectal carcinoma. Itamochi et al (2017) reported that aberrant RTK signaling was closely associated with prognosis of ovarian clear cell carcinoma and the 3-year survival rate in patients with activated RTK signaling was higher than that of patients with inactivated RTK signaling (91% vs. 53%, hazards ratio 0.35 [95% CI: 0.13-0.94], p = 0.0373). This study found comparable rates of mutation in the RTK signaling pathway in drug-resistant and -sensitive recurrent ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Activating PIK3CA mutations result in abnormal cellular growth, proliferation, survival, and angiogenesis. Interestingly, activation of either the PI3K pathway or the RTK pathway was associated with better OS, although this finding needs to be validated independently. Emerging evidence from an evaluation of 25 OCCC samples for gene expression changes and chromosomal instability suggests that OCCCs may cluster into 3 prognostic groups .…”
Section: Biologymentioning
confidence: 98%
“…Mutations in the SWI/SNF (SWItch/Sucrose Non‐Fermentable) chromatin‐remodeling complex genes, the PI3K/Akt signaling pathway, and the receptor tyrosine kinase (RTK)/Ras signaling pathway are the major molecular aberrations observed in nearly 50%, 40%, and 29% of OCCCs, respectively. Among the SWI/SNF subunits, AT‐rich interaction domain 1A ( ARID1A ) is the most frequently mutated gene, detected in 40% to 67% of OCCCs . In the PI3K signaling pathway, activating mutations in PIK3 catalytic subunit α ( PIK3CA ) (33%) and loss of phosphatase and tensin homolog ( PTEN ) (37%) are the most common aberrations .…”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the alteration of genetic profiles affected by primary therapy might influence PPS in the patients with CCC. Additionally, phosphatidylinositol-3-kinase (PI3K)/Akt signaling pathway, and the receptor tyrosine kinase (RTK)/Ras signaling pathway were identified as prognostic biomarkers for CCC tumors using whole-genome sequencing (21). Novel chemotherapeutic agents inhibiting these pathways might improve survival of the CCC patients.…”
Section: Discussionmentioning
confidence: 99%